Analysis of the Influence of Personality and Tax Morals on Student’s Tax Evasion Intentions - Jolin Floren Elvinis (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
This study aims to investigate the correlation among personality traits, tax morale, and tax evasion intentions. The dependent variable in this research is tax evasion intentions, while the independent variables consist of the five dimensions of personality based on the Big Five Personality theory (agreeableness, conscientiousness, openness, extraversion, neuroticism), along with tax morale. To conduct this research, a questionnaire was distributed to 353 active students of the 2019-2022 class from the Faculty of Business and Management at Batam International University. The questionnaire contained 35 questions and was rated using a 7-point Likert scale. The collected data were analyzed using SPSS 25, employing both multiple linear analysis and descriptive statistical analysis. The study's findings revealed a significant positive association between extraversion and tax evasion intentions. On the other hand, conscientiousness and tax morale demonstrated a significant negative correlation with tax evasion intentions. However, no significant relationship was observed between openness to experience, agreeableness, neuroticism, and tax evasion intentions. These results indicate that individuals with higher levels of conscientiousness and tax morale are less likely to engage in tax evasion, while those with higher levels of extraversion tend to have a greater inclination towards tax evasion.